Improved view frustum culling technique for real- time virtual heritage application - Sunar, Mohd. Shahrizal; Mohd. Zin, Abdullah; Tengku Sembok, Tengku Mohd. (The International Journal of Virtual Reality, 2008)
Real-time virtual heritage application is normally executed with a high performance computer system. This is due to the complexity and highly computational cost which makes such system impossible to run in a lower specification computer system. Therefore, many developed virtual heritage application cannot be retrieved by the target users. One of the factors that contribute to the high computational cost is 3D graphics processing. In this paper, a new improved technique is developed to reduce the computational cost of virtual heritage application. This technique is named as Range Detection Technique (RDT). It is based on the View Frustum Culling (VFC) method. The conventional VFC method tested the intersection of six planes using the plane equation to determine the visibility scope. Unlike conventional VFC technique, RDT is based on camera referential points and test the 3D objects whether they are in the viewing range or not. RDT execute the testing with the combination of bounding volume. Based on the testing result, a virtual heritage application with RDT can be executed with higher Frame-Per-Second (FPS) rate. The time taken to complete a set of fixed testing path is shorter. The result shows that RDT is able to increase the rendering performance and reduce the computational cost of virtual heritage application without sacrificing the visual quality Using data taken from the Ancient Malacca project, this research indirectly helps to reduce the computational cost of the former, which previously can only run with the high performance computer system.